2015
DOI: 10.1002/bkcs.10581
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivities in Fe(III)‐catalyzed Cycloisomerization Reactions of γ‐Allenyl Alcohols

Abstract: Iron-catalyzed intramolecular hydroalkoxylation reactions of allenes were performed to provide various tetrahydrofurans by regioselective 5-exo cyclization pathway, as the Lewis acidic activation of Fe(III) salts toward unsaturated C C bonds, allenes and alkenes. Cyclohexyl substituted allenes especially isomerized to dienes at a rapid rate, which underwent a competing 6-endo cyclization mode. The plausible mechanism was presented by experimental results of the reaction intermediates and computational study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…More recently Kang et al, have shown that the temperature influences the isomerisation and the endo / exo -methylene selectivity of hydroalkoxylation products of cyclohexyl-substituted allene catalysed by iron(III) tosylate ( Scheme 10 ) [ 45 ]. At 50 °C, a partial isomerisation of allenol 1 in 2 occurs and during the catalytic process, 1 is converted into tetrahydrofuran 3 via a 5- exo -trig cyclisation.…”
Section: Ironmentioning
confidence: 99%
“…More recently Kang et al, have shown that the temperature influences the isomerisation and the endo / exo -methylene selectivity of hydroalkoxylation products of cyclohexyl-substituted allene catalysed by iron(III) tosylate ( Scheme 10 ) [ 45 ]. At 50 °C, a partial isomerisation of allenol 1 in 2 occurs and during the catalytic process, 1 is converted into tetrahydrofuran 3 via a 5- exo -trig cyclisation.…”
Section: Ironmentioning
confidence: 99%
“…These available methods, however, need an additional functional group to accelerate reactivities of the Diels–Alder and consecutive reaction, and a more versatile approach was considered necessary. Inspired by our recent studies on Fe-catalyzed C–C multiple bond (allene and diene) activation, we envisaged that the relatively unactivated styrene-ynes could participate in didehydro-Diels–Alder reaction. Thus, polycyclic aromatic frameworks could be prepared using the π activation ability of the green and nontoxic iron catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This methodology is restricted to trialkylated allenols as mono-and dialkylated did not undergo cyclization under these conditions. The Fe(OTs)3 system can also be applied to the cyclization of -allenyl alcohols with concomitant alkene isomerization (Figure 3, top) [52]. During the reactivity study of -cyclohexyl-substituted allenic alcohols by this catalytic system, it was shown that the temperature influences not only the isomerization of the hydroalkoxylation products but also the endo/exo-methylene selectivity.…”
Section: Hydroalkoxylationmentioning
confidence: 99%